2018
DOI: 10.3324/haematol.2017.184192
|View full text |Cite
|
Sign up to set email alerts
|

Hide or defend, the two strategies of lymphoma immune evasion: potential implications for immunotherapy

Abstract: Evading immune eradication is a prerequisite for neoplastic progression and one of the hallmarks of cancer. Here, we review the different immune escape strategies of lymphoma and classify them into two main mechanisms. First, lymphoma cells may “hide” to become invisible to the immune system. This can be achieved by losing or downregulating MHC and/or molecules involved in antigen presentation (including antigen processing machinery and adhesion molecules), thereby preventing their recognition by the immune sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 176 publications
(217 reference statements)
2
64
0
1
Order By: Relevance
“…However, consistent with findings from other studies, bone marrow involvement at baseline was similar here for low versus normal/high baseline peripheral blood NKCC in follicular lymphoma and DLBCL, suggesting that other mechanisms are involved. It has been shown that lymphoma cells may block maturation of NK cells in the bone marrow by interrupting pathways necessary for their development or via mechanisms leading to direct inhibition or killing of immune cells, including NK cells (35,36). These mechanisms operate differently in follicular lymphoma and DLBCL, as well as in particular COO subtypes (36), and thus may contribute to different levels of host immune suppression in B-NHL subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, consistent with findings from other studies, bone marrow involvement at baseline was similar here for low versus normal/high baseline peripheral blood NKCC in follicular lymphoma and DLBCL, suggesting that other mechanisms are involved. It has been shown that lymphoma cells may block maturation of NK cells in the bone marrow by interrupting pathways necessary for their development or via mechanisms leading to direct inhibition or killing of immune cells, including NK cells (35,36). These mechanisms operate differently in follicular lymphoma and DLBCL, as well as in particular COO subtypes (36), and thus may contribute to different levels of host immune suppression in B-NHL subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that lymphoma cells may block maturation of NK cells in the bone marrow by interrupting pathways necessary for their development or via mechanisms leading to direct inhibition or killing of immune cells, including NK cells (35,36). These mechanisms operate differently in follicular lymphoma and DLBCL, as well as in particular COO subtypes (36), and thus may contribute to different levels of host immune suppression in B-NHL subtypes. In line with this, we observed that patients with follicular lymphoma and DLBCL with low baseline peripheral blood NKCCs had adverse clinical characteristics compared with patients with normal/high NKCCs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, cancers evade the host immune system through mechanisms of apoptotic resistance and immune cell deactivation. Specifically, however, hematological malignancies result in metabolic changes that directly suppress effector immune responses [ 27 , 29 , 45 , 46 , 47 ]. Rapidly dividing cancer cells increase the expression of immune inhibitory molecules which skew the balance of immune activation to promote immune dysregulation.…”
Section: Unbalanced Immune Responses In Autoimmune and Systemic Comentioning
confidence: 99%
“…Overcome immunotherapy resistance in B-cell lymphoma REVIEW classical Hodgkin lymphoma (HL) present the loss of MHC class I expression (Challa-Malladi et al, 2011;de Charette and Houot, 2018), and diminished MHC class II expression also frequently occurs not only in DLBCL but also in other types of mature B-cell lymphomas (Rimsza et al, 2004;Roberts et al, 2006;Diepstra et al, 2007a;Fangazio et al, 2014;de Charette et al, 2016;Nijland et al, 2017). We recently established a unique mouse model by lineagespecific deletion of a DNA repair gene, Xrcc4, and Trp53 in GC B cells (Chen et al, 2016).…”
Section: Cellmentioning
confidence: 99%